Broad-Spectrum Antimicrobial and Antibiofilm Activity of a Natural Clay Mineral from British Columbia, Canada - Shekooh Behroozian (American Society for Microbiology, 2020)
ABSTRACT Worldwide increases in antibiotic resistance and the dearth of new antibiotics have created a global crisis in the treatment of infectious diseases. These concerns highlight the pressing need for novel antimicrobial agents. Natural clay minerals have a long history of therapeutic and biomedical applications and have lately received specific attention for their potent antimicrobial properties. In particular, Kisameet clay (KC) has strong antibacterial activity against a variety of multidrug-resistant (MDR) bacterial pathogens in vitro. Here, we have extended the known spectrum of activity of KC by demonstrating its efficacy against two major fungal pathogens, Candida albicans and Cryptococcus neoformans. In addition, KC also exhibits potent activity against the opportunistic bacterial pathogen Mycobacterium marinum, a model organism for M. ulcerans infection. Moreover, aqueous KC leachates (KC-L) exhibited broad-spectrum antibacterial activity, eradicated Gram-negative and Gram-positive biofilms, and prevented their formation. The mechanism(s) underlying KC antibacterial activity appears to be complex. Adjusting KC-L to neutral pH rendered it inactive, indicating a contribution of pH, although low pH alone was insufficient for its antibacterial activity. Treatment of KC minerals with cation-chelating agents such as EDTA, 2,2′-bipyridyl, and deferoxamine reduced the antibacterial activity, while supplementation of KC-L with these chelating agents eliminated the inhibitory activity. Together, the data suggest a positive role for divalent and trivalent cations, including iron and aluminum, in bacterial inhibition by KC. Collectively, these studies demonstrate the range of KC bioactivity and provide a better understanding of the mechanism underlying its antibacterial effects. IMPORTANCE The escalating emergence of multidrug-resistant (MDR) bacteria, together with the paucity of novel antimicrobial agents in antibiotic development, is recognized as a worldwide public health crisis. Kisameet clay (KC), found in British Columbia (BC), Canada, is a clay mineral with a long history of therapeutic applications among people of the First Nations. We previously reported the antibacterial activity of KC against a group of MDR clinical pathogens. Here, we demonstrate its activity against two major human-pathogenic fungal species, as well as against bacterial biofilms, which underlie many recalcitrant bacterial infections. In these studies, we also identified several geochemical characteristics of KC, such as metal ions and low pH, which are involved in its antibacterial activity. These findings provide a better understanding of the components of KC antibacterial activity and a basis for developing defined preparations of this clay mineral for therapeutic applications.